Optimization of VCO, TWEEN 80, and PEG 400 Nanoemulsion Formulation of Gemitir Flower Extract (Tagetes Erecta L.) with Simplex Lattice Design - Putu Ayu Ratih Listiani; Putu Ika Indah Indraswari; Made Dwike Swari Santhi; Gusti Ayu Oviani; Sri Suwarni (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Tagetes erecta L. (Gemitir flower) is known to have potential antibacterial activity; however, its use in topical preparations is limited by low solubility and stability. Objective: This study aims to optimize the nanoemulsion formulation of Gemitir flower extract using virgin coconut oil (VCO) as the oil phase, Tween 80 as the surfactant, and PEG 400 as the cosurfactant. Methods: Phytochemical screening, antibacterial activity testing against Staphylococcus aureus, total flavonoid determination, and nanoemulsion formulation optimization were conducted using the Simplex Lattice Design method with Design Expert® software version 13 to evaluate the effects of VCO, Tween 80, and PEG 400 combinations on the physical characteristics of the nanoemulsion. Results: The optimal formulation was obtained with a composition of VCO 0.53 g, Tween 80 8 g, and PEG 400 4 g, with a desirability value of 0.990. The resulting nanoemulsion showed a transmittance value of 97.56%, entrapment efficiency of 1.46%, pH of 5.26, and no phase separation during storage (score = 1). The homogeneity test confirmed a uniform preparation, and the emulsion type test indicated an oil-in-water (O/W) system. Conclusion: The nanoemulsion formulation of Gemitir flower extract using VCO, Tween 80, and PEG 400 optimized through Simplex Lattice Design produced a system with appropriate physical characteristics for topical antibacterial application. However, further studies on particle size, zeta potential, and long-term stability are recommended.